Cancer Chemopreventive Properties of Sulfated Enterolobium cyclocarpum Extract. (10th March 2021) - Gamal-Eldeen, Amira M.; Amer, Hassan; Alrehaili, Amani A; Saleh, Ahmed; Al Ghamdi, Abd El-Rahman; Hawsawi, Nahed M; Salman, Asma; Raafat, Bassem M.
Abstract: Enterolobium cyclocarpum (EC) is an edible plant and a gum source for food industries. Its sulfated polysaccharide extract (SEC) was examined for cancer chemopreventive properties to estimate its anti-tumor activity. The modulation of carcinogen metabolism and the antioxidant activity revealed that SEC is a potent tumor anti-initiator since it inhibited cytochrome P450-1A (CYP1A) and induced carcinogen detoxification enzyme glutathione-S-transferase. SEC is also a weak scavenger for hydroxyl and peroxyl radicals. SEC was found to modulate macrophage functions into an anti-inflammatory pattern, where it enhanced macrophage proliferation and phagocytosis of fluorescein isothiocyanate-lipopolysaccharide (FITC-LPS). In addition, SEC strongly inhibited the nitric oxide (NO) generation in LPS-stimulated macrophages and induced the binding affinity of FITC–LPS to macrophages. SEC exhibited specific cytotoxicity against human hepatocellular Hep G2 carcinoma cells. SEC disturbed the cell cycle phase, as indicated by the concomitant arrest in S- and G2/M-phases that was associated with necrosis induction. A short-term initiation model for liver cancer was prepared using diethylnitrosamine (DEN) in rats. SEC inhibited the DEN-histopathological findings and reduced both CYP1A and the tumor initiation marker placental glutathione S-transferase (GSTP). Taken together, SEC could be used as an alternative gum in health food industries to provide cancer prevention in high-risk populations.